2009
DOI: 10.1161/strokeaha.108.535435
|View full text |Cite
|
Sign up to set email alerts
|

SK Ca and IK Ca Channels, Myogenic Tone, and Vasodilator Responses in Middle Cerebral Arteries and Parenchymal Arterioles

Abstract: Background and Purpose-The role of SK Ca and IK Ca channels in myogenic tone and endothelium-derived hyperpolarizing factor (EDHF) responsiveness was investigated under control conditions and after ischemia and reperfusion in parenchymal arterioles (PA) versus middle cerebral arteries (MCA). Methods-MCA and PA were dissected from male Wistar rats that were ischemic for 1 hour with 24 hours of reperfusion (nϭ12) or sham controls (nϭ12). Basal tone and reactivity to apamin (300 nmol/L), TRAM-34 (1.0 mol/L), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(178 citation statements)
references
References 26 publications
14
164
0
Order By: Relevance
“…To our knowledge, no study has addressed the effects of hypertension on NVC mechanisms solely in PAs. Given that myogenic responses are dependent upon arteriole size 10 and mediated by different mechanisms in pial arterioles versus PAs, 11,12 understanding hypertension-induced brain pathologies in discrete cerebrovascular beds is essential. In the present study, we demonstrated that in SHR PAs: (1) U46619-induced tone and basal VSMC Ca 2+ oscillation frequency were higher, (2) myogenic tone was enhanced, (3) wall-to-lumen ratio and wall thickness were increased, (4) K + -induced dilations were not impaired, (5) t-ACPD-induced dilations were enhanced, and (6) neuronal activation-induced dilations were not impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no study has addressed the effects of hypertension on NVC mechanisms solely in PAs. Given that myogenic responses are dependent upon arteriole size 10 and mediated by different mechanisms in pial arterioles versus PAs, 11,12 understanding hypertension-induced brain pathologies in discrete cerebrovascular beds is essential. In the present study, we demonstrated that in SHR PAs: (1) U46619-induced tone and basal VSMC Ca 2+ oscillation frequency were higher, (2) myogenic tone was enhanced, (3) wall-to-lumen ratio and wall thickness were increased, (4) K + -induced dilations were not impaired, (5) t-ACPD-induced dilations were enhanced, and (6) neuronal activation-induced dilations were not impaired.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, the effects of hypertension on NVC-mediated vasodilations have yet to be investigated solely in the distinct subpopulation of cerebral microvessels penetrating the brain parenchyma, the parenchymal arterioles (PAs). Given that artery size is an important determinant of cerebral myogenic responses 10 and that myogenic tone is mediated by different mechanisms in pial arterioles versus PAs, 11,12 the importance of studying hypertension-induced brain pathologies in discrete vascular beds should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…10 In contrast, isolated, pressurized middle cerebral arteries do not constrict to IK and SK channel inhibition, suggesting that these channels are not tonically active under basal conditions in larger surface arteries. 124 In mesenteric arteries, the SK3 subtype has been identified at MEPs and EC-EC borders. 125 The loss of apamin-sensitive K Ca currents in mesenteric ECs from an SK3 gene suppression mouse confirms that this is the primary SK isoform for the regulation of vascular tone.…”
Section: Trpv4 Channelsmentioning
confidence: 99%
“…Moreover, because NO-cGMP-PKG signaling has been reported to inhibit TRPV4 channels (alone 159 or when complexed with TRPC1 160 or TRPP2 161 ), endothelial and endfoot Ca 2þ signaling could also be affected. Recent work has identified a contribution of eNOS signaling to resting tone in isolated pressurized middle cerebral arteries and parenchymal arterioles, 124 but whether NO is actively recruited during NVC is controversial. 149,162,163 However, emerging evidence supports the concept of endothelial engagement during NVC through the release of parenchymal factors that increase eNOS activity.…”
Section: Nitric Oxide: Nvc Mediator or Modulator?mentioning
confidence: 99%
“…Several observations point to the fact that EDH is a major regulator of CBF: (1) EDH is more important than NO as a dilator mechanism in isolated PA upon activation of P2Y2 receptors (You et al, 1999); (2) EDH contributes to resting CBF and the resting tone of arterioles (Hannah et al, this issue) (Cipolla and Bullinger, 2008;Cipolla et al, 2009); (3) EDH is as important as NO in controlling resting CBF (Hannah et al, this issue); and (4) EDH dilations persist or are even upregulated in cerebral vessels, following a number of pathological states, when NO bioavailability is diminished (Cipolla and Bullinger, 2008;Cipolla et al, 2009;Golding et al, 2001;Marrelli et al, 1999;Prisby et al, 2006). Thus, EDH must be considered as a significant mechanism for the regulation of CBF and as a potential target for increasing CBF in pathological states where flow has been compromised.…”
mentioning
confidence: 99%